Pengaruh Kualitas Pelayanan, Persepsi tentang Biaya dan Citra terhadap Kepuasan dan Loyalitas Pengguna (Studi pada Instalasi Rawat Jalan RSUD Dr. Saiful Anwar Malang) - Hidayat, Hanan Titis (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
A goverment has an obligation to guarantee healthy right live to citizens. An empirict fact shows that service is given from hospital state has not fulfilled hopes yet. The purpose of this research to know an influence service quality, a perception about cost and image in satisfying and loyality users in IRJ RSSA. This quantitave research is from a survey 100 respondents are as samples. Data is analized on correlation tests, simple linier regretion, double linier regretion and Manova. The result of research shows on parcial and simultant variable, service quality, a perception about financial and image influence positive significant to satisfying and loyality users. An parcial view, satisfing has dominant qualities to be loyality user’s. Therefore, any suggestions we say that : 1) for next researchers who will examine about satisfaction and loyalty, should consider other variables, 2) RSSA need to repair service quality, and 3) need a improving service access and societies program.